Design of power light emitting diode (LED) emergency lighting system incorporating peripheral interface controller (PIC) / Ahmad Nasri Mahmad - Mahmad, Ahmad Nasri (2009)
This paper presents the project design and fabricates an emergency lighting system to backup when the other forms lighting is off due to the occurrence of temporary power outage. By using power LED as bulb rather than conventional lighting such as fluorescent, it helps to extend the duration of light output while maintaining the brightness of the lightning as its luminous intensity per watt are higher than fluorescent. The power adaptor supplying 14 Volt output is used to recharge the battery. The battery is needed to power up the LED and the circuit of the emergency lighting system when there is a power outage. PIC microcontroller with MPLAB programming software is used as system control of the circuit. The device operates in three different modes which is standby mode, charging mode and operation mode. The information of the project is obtained from internet, journals and books. The calculations of the parameters also had been performed in order to program the emergency lighting system.